Influence of perceived quality and self-esteem on women’s purchase intention: Luxury makeup brands / Shahira Shahina Mobil … [et al.] - Mobil, Shahira Shahina; Kasuma, Jati; Adenan, Mohd Amirul; Mejri, Norazimah; Rajan, Rohanna (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2019)
Luxury brands have often been associated with the core competences of creativity, exclusivity, craftsmanship, precision, high quality, innovation and premium pricing. These product attributes give consumers the satisfaction of not only owning expensive items but the extra-added psychological benefits like esteem, prestige and a sense of a high status that reminds them and others that they belong to an exclusive group of only a select few, who can afford these premium items. Thus, this research aims to investigate the relationship between and influence of Perceived Quality and Self Esteem on luxury branded makeup purchase. Data from 141 questionnaires were completed by women living in Kuala Lumpur. The findings of the study showed that perceived quality and self-esteem have significant effects on consumers’ intention towards buying luxury branded makeup. Implication and areas for future research are further discussed.